2019
DOI: 10.1016/j.purol.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Dysfonctions sexuelles après traumatisme crânien : revue systématique de la littérature

Abstract: Background: Sexual dysfunctions (SD) are common after a traumatic brain injury (TBI) but remain underrated in clinical practice, yet it is a crucial aspect of the person with consequences for the relationship with the other, psychological well-being and quality of life. Objective: To determine, through a systematic literature review, the epidemiology, assessment tools and treatment of SD in the TBI population. Sources (keywords, languages): MEDLINE, COCHRANE and OVID databases were used with Limits: Quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
2
0
1
Order By: Relevance
“…For instance, in traumatic brain injury (TBI), many studies have been conducted. In a recent review, Robert et al [ 58 ] demonstrated that following TBI, between 6% and 83% of patients suffer SD, including decreased frequency of sex (47–62%), decreased desire and/or arousal (24–86%), erectile dysfunction (24–57%), difficulty with orgasm (29–40%), and inappropriate sexual behavior (8–9%). SD is positively associated with mood disorders and cognitive-behavioral therapy has been proposed as the best therapeutic approach for these patients.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…For instance, in traumatic brain injury (TBI), many studies have been conducted. In a recent review, Robert et al [ 58 ] demonstrated that following TBI, between 6% and 83% of patients suffer SD, including decreased frequency of sex (47–62%), decreased desire and/or arousal (24–86%), erectile dysfunction (24–57%), difficulty with orgasm (29–40%), and inappropriate sexual behavior (8–9%). SD is positively associated with mood disorders and cognitive-behavioral therapy has been proposed as the best therapeutic approach for these patients.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…In fact, not all studies were able to find a difference in urinary calcium excretion between calcium oxalate stone formers with and without Randall's plaque respectively [19,149] and urinary calcium excretion in Abcc6 − / − was not different compared to wild type mice, suggesting that hypercalciuria is insufficient for the development of Randall's plaque and that additional deficiency of inhibitors like inorganic pyrophosphate is mandatory. Low urinary levels of inorganic pyrophosphate have been reported in stone formers [150][151][152][153], but currently it is unknown if patients with Randall's plaque display lower urinary levels of inorganic pyrophosphate compared to patients with stone formation unrelated to Randall's plaque. Measurement of inorganic pyrophosphate levels has been difficult in the past due to absence of reliable methods and the very low concentrations of inorganic pyrophosphate.…”
Section: Development Of An Animal Model and The Role Of Inorganic Pyrophosphatementioning
confidence: 99%
“…Cependant, il n'existe pas à l'heure actuelle d'outils validés en français pour évaluer ces dysfonctions sexuelles, ni de recommandations sur le traitement. (17) Les professionnels de la réhabilitation trouvent compliqué de traiter avec les troubles de la sexualité liés au TC, et les raisons sont complexes et inter-reliées (18). Les discussions sur la sexualité devraient être comprises dans les entretiens, et de l'information écrite devrait être à la disposition des bénéficiaires.…”
Section: Introductionunclassified